Correct spelling of a recently described species of Helobdella (Annelida: Clitellata: Hirudinea) - Saglam, Naim; Kutschera, Ulrich; Saunders, Ralph; Saidel, William M.; Balombini, Katherine L.w.; Shain, Daniel H. (Zootaxa, 2019)
In a recently published article (Saglam et al. 2018) the name of a new species of Hirudinea (Annelida, Clitellata) was simultaneously published in three different ways, as Helobdella serendipitious (Saglam et al. 2018: 61, 70, 71, 73), Helobdella serendipitous (ibid.: 63, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74), and as Helobdella serendipidous (ibid.: 75). Acting as first reviser according to Article 24 of the International Code of Zoological Nomenclature (ICZN 1999) here we determine serendipitous as the correct spelling of the species epitheton.